A test model for telecentre value creation - Md Dahalin, Zulkhairi; Yusop, Nor Iadah; Ibrahim, Huda; Mat Aji, Zahurin; Othman, Nafishah; Bakar, Rosmadi; Md Yussop, Yussalita; Kasiran, Mohd Khairudin (2015)
This paper presents results of a research to create a model for telecentre value creation. The aim is to study the effect of diffusion and adoption of information and communication technology through telecentre implementation. The National Strategic Framework for Bridging Digital Divide states that the socio-economic value could not achieve its optimal level when the focus is on diffusion.Hence this study attempts to determine the effect of diffusion and adoption on value creation individually and combined.A conceptual model was developed based on review of related literatures and then operationalized into research variables that form the questionnaire.A survey was administered and descriptive and multivariate analyses were conducted to examine the model fit and verify the model for telecentre value creation. Results of the study found compelling strong relationships on both diffusion and adoption with value creation with adoption have stronger effect on value creation as compared to diffusion.